Begonia amparoi (Begoniaceae, section Baryandra) a new species from Linungaw Twin Islands, Surigao del Sur, Mindanao, Philippines - Blasco, Freddie A.; Alejandro, Grecebio Jonathan D.; Tandang, Danilo N.; Vales, Marianita B.; Rubite, Rosario R. (Phytotaxa, 2022)
We describe Begonia amparoi, a new species of Begonia section Baryandra from Linungaw Twin Islands, Mindanao, Philippines. It grows on limestone and has a robust habit, with a thick rhizome and large leaves. Begonia amparoi is currently known only from the type locality in a coastal island forest of Tandag City, Province of Surigao del Sur. Based on IUCN red list criteria, B. amparoi is considered Vulnerable (VU).